Linkages with Micro Small Medium Enterprises (MSMEs) for Sustainable Higher Education in Management - Shivany, S. (University of Jaffna, 2021)
This chapter explains the imperative of linking with micro small medium enterprises (MSMEs) as vital contributors to the process of commercialization of new knowledge discovered in the higher education sector. Higher education in management has the greatest challenge to equalize graduates’ knowledge and skills with existing employment opportunities. MSMEs are job creators in the economy and contributors to sustainable development. If the education system of higher education in management does not withstand future needs, this will impair the social, economic, and environmental conditions of the country. To sustain the balance in these three pillars of sustainability, management graduates who will be future managers should be educated well with the needed skills and knowledge through a sustainable curriculum, which can be enriched with the linkage with the MSMEs during study, a milestone for business startup, employment opportunities, and industry intakes.
Keywords: MSMEs Linkages; Sustainable higher education; Management